2022
DOI: 10.54910/sabrao2022.54.5.20
|View full text |Cite
|
Sign up to set email alerts
|

Response of Peanut to Weed Control Management and Nano-Zinc Foliar Application in Growth, Yield, and Quality Traits

Abstract: A field experiment on a local peanut (Arachis hypogaea L.) cultivar transpired in the spring season of 2021 at the Al-Hussainiya region, Holy Kerbala, Iraq (Latitude: 32.6160; Longitude: 44.0249). The completed study aimed to determine peanut response to weed control, foliar application of nano-zinc, and their interaction in growth, yield, and quality traits. The experiment laid out in a split-plot design with two factors (weed control and nano-zinc foliar application) had three replications. The nano-zinc con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Also, the plant's dry weight escalated with the addition of nitrogen. It is due to its role in increasing the height and branches of plants and thus enhancing their vegetative growth, leading to an increase in dry weight (Basal and Szabó, 2020;Mondal et al, 2020;Al-Yasari et al, 2022;Elnagar et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the plant's dry weight escalated with the addition of nitrogen. It is due to its role in increasing the height and branches of plants and thus enhancing their vegetative growth, leading to an increase in dry weight (Basal and Szabó, 2020;Mondal et al, 2020;Al-Yasari et al, 2022;Elnagar et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of movement of materials represents the photosynthesis process from the source, which is the root of the estuary. Thus, the growth is abnormal, the competition is low, and the dry weight of the weeds is reduced 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Peanut (Arachis hypogaea L.) of substantial economic value in the world, returns to the Leguminosae, which is of high nutritional value, as its seeds contain (45-50)% oil, (27)(28)(29)(30)(31)(32)(33))% protein and a primary source of minerals and vitamins 1 , Iraq consumes large quantities of this crop, more than 40 thousand tons annually, to be used in oil extraction, It is hoped that the cultivated area in Iraq of this crop will increase due to the increased demand for it for its multiple industrial benefits 2 , which is limited compared to the countries producing this crop, The production of the field Peanut annually is about 41.9 million tons and contributes 7.3 % of the total oil seed production in the world for the year 2018 3 . Iraq consumes large quantities of this crop, more than 40 thousand tons annually, for oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Packaging contributes to keeping the fruit peel clean and smooth, being one of the most successful methods to produce pollution-free and high-quality fruits [59]. In fact, packaging is widely used worldwide, especially for apples, pears, and pomegranates [60][61][62]. It has been observed that when pomegranates are packaged in red, the rate of peel cracking decreases by a third, and the ascorbic acid content and anthocyanins increases to the highest level [63,64].…”
Section: Plastic Covers and Packagingmentioning
confidence: 99%